2023
DOI: 10.1186/s12875-023-01968-z
|View full text |Cite
|
Sign up to set email alerts
|

Primary care team and its association with quality of care for people with multimorbidity: a systematic review

Abstract: Background Multimorbidity is posing an enormous burden to health systems, especially for primary healthcare system. While primary care teams (PCTs) are believed to have potentials to improve quality of primary health care (PHC), less is known about their impact on the quality of care for people with multimorbidity. We assessed the characteristics of PCTs and their impact on the quality of care for people with multimorbidity and the mechanisms.  Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…However, despite variations in the organizational context, the informants at P1, P2, P3, and P4 agreed that functional teamwork produced good and relevant results, primarily for the patients as well as Team Effectiveness in General Practice: Insights from the Norwegian Primary Healthcare Team… DOI: http://dx.doi.org/10.5772/intechopen.1004545 largely for themselves as it increased their job satisfaction. These results are in line with findings in other studies [4,15,34,40]. The stories told by the informants at P1 and P2 indicate an increase over time in their ability to collaborate.…”
Section: Discussionsupporting
confidence: 92%
“…However, despite variations in the organizational context, the informants at P1, P2, P3, and P4 agreed that functional teamwork produced good and relevant results, primarily for the patients as well as Team Effectiveness in General Practice: Insights from the Norwegian Primary Healthcare Team… DOI: http://dx.doi.org/10.5772/intechopen.1004545 largely for themselves as it increased their job satisfaction. These results are in line with findings in other studies [4,15,34,40]. The stories told by the informants at P1 and P2 indicate an increase over time in their ability to collaborate.…”
Section: Discussionsupporting
confidence: 92%
“…Often, these patients are being managed in a highly fragmented manner, with each healthcare professional focused on a single pathology and, therefore, these patients are subjected to a greater number of negative outcomes [ 13 ]. As results of a systematic review [ 42 ], a wide range of healthcare components were found to have the potential to improve services: individual care plans, thorough geriatric assessments, and the application of shared decision-making [ 37 , 43 , 44 ]. Here, the priority for health systems is to deliver people-centred primary care services.…”
Section: Discussionmentioning
confidence: 99%
“…Som vist i forsøket, kan teamarbeid også bidra til økt arbeidstilfredshet. Dette er i tråd med funn fra internasjonal litteratur (Li et al, 2023;O'Malley et al, 2015;Weller et al, 2014;Schmutz et al, 2019). Dersom team arbeid kan gjøre arbeid i den kommunale helse-og omsorgstjenesten mer attraktivt og redusere utskifting av ansatte, kan dette bidra til å styrke tjenesten fremover.…”
Section: Styrker Og Svakheter Ved Forsøketunclassified